Don't worry, little crab - Haughton, Chris (Candlewick Press, 2020)
"Little Crab and Very Big Crab live in a tiny rock pool near the sea. Today they're going for a dip in the big ocean. 'This is going to be so great, ' says Little Crab, splish-splashing and squelch-squelching along, all the way to the very edge. Then comes a first glance down at the waves. WHOOSH! Maybe it's better if they don't go in? With vivid colors, bold shapes, and his trademark visual humor, Chris Haughton shows that sometimes a gentle 'don't worry, I'm here' can keep tentative little crabs sidestepping ahead--and help them discover the brilliant worlds that await when they take the plunge."--Amazon.